2019
DOI: 10.2166/wst.2019.131
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus recovery from the sludge generated from a continuous bipolar mode electrocoagulation (CBME) system

Abstract: Phosphorus is known to be a limited non-renewable resource. Phosphorus is obtained from phosphate rock, which is likely to be depleted in the next few decades. Therefore, it is very important to find alternate sources of phosphorus from which phosphorus can be recycled and recovered. This study focuses on the recovery of phosphorus from the sludge generated from a continuous bipolar mode electrocoagulation (CBME) system, used for treating a palm oil mill effluent (POME). The sludge generated from the CBME syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…POME, even after pre-treatment, is rich in nutrient parameters such as nitrogenous and phosphorus compounds (Yashni et al, 2020). A recent study has reported the recovery of phosphorus from POME through combustion of the sludge, followed by acid leaching and extraction using sulphuric and oxalic acids (Damaraju et al, 2019).…”
Section: Recovery Of Useful Chemicals and Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…POME, even after pre-treatment, is rich in nutrient parameters such as nitrogenous and phosphorus compounds (Yashni et al, 2020). A recent study has reported the recovery of phosphorus from POME through combustion of the sludge, followed by acid leaching and extraction using sulphuric and oxalic acids (Damaraju et al, 2019).…”
Section: Recovery Of Useful Chemicals and Nutrientsmentioning
confidence: 99%
“…Among the many and more recent treatment alternative techniques are the biological options of (an)aerobic therapies and chemical techniques. While some of the techniques of choice must, within a reasonable timeframe, offer the best results in terms of waste management -reduction in chemical oxygen demand (COD) and biochemical oxygen demand (BOD), others assist in useful product recovery including but not limited to biofuels, biofertilizers, and bioproducts (Ahmad et al, 2020;Damaraju et al, 2019;Hope & Gideon, 2015;Ndubuisi-Nnaji et al, 2020). Various methodologies have been studied for developing low-priced and active treatment techniques, including the integrated anaerobic-aerobic bioreactor (IAAB) system.…”
Section: Introductionmentioning
confidence: 99%
“…Gorazda et al [62] reported a combustion temperature of 950 °C as the best condition for downstream phosphorus extraction from ash. Acid leaching resulted in nearly 85% recovery of P with both sulphuric acid and oxalic acid for sludge combusted at 900 °C [63]. Kasina et al [64] investigated the chemical and mineralogical characteristics of ISSA obtained from Veolia's fluidized bed incinerator for SS (Pyrofluid) at 850-900 °C and concluded that elements which are characterized by high melting temperatures concentrate in the ISSA, while elements that are characterized by lower melting temperatures (e.g.…”
Section: Incinerationmentioning
confidence: 99%